OPPORTUNITIES FOR EXTRACURRICULAR EDUCATIONAL WORK HIGHER EDUCATIONAL INSTITUTION IN THE FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS - O.O. Havrylyuk (Academy of Cognitive and Natural Sciences, 2007)
At this article is considered components of educational work of university and so its possibilities on a way of forming of communicative culture of students.